Factors Associated with Ovarian Hyperstimulation Syndrome (OHSS) Severity in Women With Polycystic Ovary Syndrome Undergoing IVF/ICSI - Sun, Bo; Ma, Yujia; Li, Lu; Hu, Linli; Wang, Fang; Zhang, Yile; Dai, Shanjun; Sun, Yingpu (Frontiers in Endocrinology, 2021)
Introduction: Age, polycystic ovary syndrome (PCOS), low body mass index (BMI), high antral follicle count (AFC), increased anti-Muller hormone (AMH) levels and elevated serum estradiol (E2) concentrations are risk factors for ovarian hyperstimulation syndrome (OHSS). However, data on the relationship between risk factors and OHSS severity in patients with PCOS are rare. Objective: This retrospective study examined the risk factors for OHSS and their effect on OHSS severity in patients with PCOS undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI). Method: The records of 2,699 women were reviewed and included in this study. These women were diagnosed with PCOS during their first IVF/ICSI cycle between January 2010 and December 2017. We analyzed the association between each of the interrogated risk factors (including female age, BMI, AFC, basal serum E2, and the number of oocytes retrieved) and OHSS. The effects of each risk factor on OHSS severity were further explored. Logistic regression was performed as part of the above analysis. Results: Of the 2,699 women with PCOS who underwent assisted reproductive technology (ART), 75.2% had a normal response to controlled ovarian hyperstimulation (COH), while 24.8% developed OHSS. All OHSS patients were younger and had lower BMIs and basal serum follicle-stimulating hormone (FSH) and E2 levels but higher AFCs than those in the normal group. AFC demonstrated a strong correlation with OHSS, with a cutoff value of 24 in patients with PCOS. A total of 19.5% of the patients had mild OHSS, while 80.5% had moderate OHSS. Compared with those in the moderate OHSS group, those in the mild OHSS group were older and had higher basal serum FSH levels and lower serum E2 and T levels. However, BMI and AFC were not different between the mild and moderate OHSS groups. Basal serum E2 showed a strong correlation with OHSS severity, with a cutoff value of 37.94 pg/ml. Conclusions: AFC is a strong marker of OHSS, and basal serum E2 is the best predictor of OHSS severity in women with PCOS undergoing IVF treatment.